Homo Dialogicus: Philosophical Investigations - Nandhikkara, Jose (Journal of Dharma, 2017)
Human beings are social beings and dialogue in all its forms is fundamental to human life and well being. Co-reflection, conversation and collaboration are fundamental forms of human lives and means to live in harmony. Dialogue is not borne of a particular act of will; it is part of human nature. It is not just that we have, besides other faculties and skills, also the one of dialogue; it is dialogue that makes a being a human being, and contributes to better personalisation and socialization.